Integration of artificial intelligence in biodegradable plastic packaging design: exploring stakeholder attitudes - Ulfy, Mohammad Arije; Haque, A. K. M. Ahasanul; Huda, Md. Nazmul (RSIS International, 2025)
Biodegradable plastic or biopolymers from renewable resources have attracted growing interest from industries as well as individual consumers as a solution to the environmental problems and limited resources of petroleum-based polymers. This research aims to explore stakeholder attitudes towards the integration of artificial intelligence (AI) in biodegradable plastic packaging design, aiming to address gaps in sustainable packaging innovation. This study engaged 30 principal players, comprising packaging designers, sustainability officers, lawmakers, NGO representatives, and ecologically aware customers. The researchers employed a multi-method qualitative framework, encompassing comprehensive case studies of five organisations at various levels of AI deployment and a phenomenological analysis of stakeholder experiences. The data gathering encompassed semi-structured interviews, focus group discussions, and the analysis of business sustainability reports and policy documents. The results identified three major stakeholder groups: hopeful industrial pragmatists, cautious reformers, and sceptical consumers. Significant obstacles included knowledge disparities between technical and executive teams, regulatory ambiguities, and workforce transfer apprehensions. Consequences for practice include methods for implementing artificial intelligence in stages, open certification systems, and legislative subsidies for ethical innovations.